Soft Tissue Nose and Chin Thickness in Adult Orthodontic Patients with Various Mandibular Growth Patterns - Bajracharya, Manju; Pradhan, Resina; Maharjan, Surendra; Pant, Bashu Dev (Orthodontic Journal of Nepal, 2025)
Introduction: Individuals with various mandibular growth patterns may require Orthognathic surgery to improve nose and chin thickness to compensate for increased mandibular divergence. Determining soft tissue nose and chin thickness is crucial in these situations. This study was conducted to evaluate soft tissue nose and chin thickness of patients with mandibular divergences and their association between and within different genders of orthodontic patients visiting People’s Dental College and Hospital. Materials and Methods: A descriptive cross-sectional study was conducted from 12th Oct 2023 to 12th Sept 2024 at People’s Dental College and Hospital. A convenience sampling method was used to collect 291 samples (pre-treatment lateral cephalograms of 158 females, 133 male patients) age ranging between 18 to 30 years. Nose and chin parameters were analyzed, measured with SPSS 16 version software, using an independent student’s t-test to find out any statistical difference (p<0.05) between various mandibular divergences. Results: Among 291 subjects, 63 (males 29, females 34) had hypodivergent, 99 (29 males, 70 females) normodivergent, 129 (73 males, 56 females) hyperdivergent growth patterns. Soft tissue nose thickness was greater in females than in males among various mandibular divergence patterns (p<0.05), while soft tissue chin thickness in males was greater at the level of Pog, Gn, in hypodivergent, at the level of Me in hyperdivergent than in female samples. Within the same genders, no significant difference in soft tissue nose among various mandibular divergences, soft tissue chin thickness at the level of Pog in hypodivergent males was greater compared to normodivergent males. At the level of Gn, Me, normodivergent females had greater chin thickness than hyperdivergent females. Conclusion: The soft tissue nose and chin thickness were variable in different levels of chin between and within genders among various mandibular divergences.